VIII Bogd Javzandamba became Mongolia`s political leader - Ayush, Khishigdavaa (Studia Philosophiae Et Juris, 2024)
VIII Bogd Javzandamba was an important politician who made Mongolia a free and independent country. Since the 1900s, the State has pursued foreign and domestic policies aimed at ensuring national freedom and independence, and has achieved results and success. Bogd Javzandamba is not only a religious figure, but also a political and social leader. This document focuses on the views of "political leaders". In the early 20th century, Bogd Javzandamba was recognized as a prominent religious, political and social figure not only in Mongolia, but also in Mongolia. He not only led the spirit of society, but he had a circle of rulers, followers, faithful supporters, and citizens. Manchu also worked for the Qing Government, but sought independence by securing support from Mongolia's Prince, Government officials, and military and religious figures. The success, success and value of the 1911 National Liberation Revolution were based on their ability to unite their views and objectives. The political policy of Bogd Javzandamba is evident in the political, economic and military activities of colleagues such as Chin van Khanddorj, Da Lama Tserenchimed, Sain noyon Khan Namnansuren, Tushee Chagdarjav and Chaisan Gun. According to historical facts, the aim was to establish the “Mongolian Tuurgatan” state, which included not only the interior of Mongolia, but also the interior of Mongolia, Buriad and Tagna Uriankhai. Although this goal has not yet been fully achieved, it is a great achievement that he removed Mongolia from the Qing Dynasty of Manchu in over 200 years and declared its independence. Bogd Javzandamba was not only the leader of the 1911 National Liberation Revolution, but also a political leader who had a significant influence and dynamism in the 1921 People's Revolution. VIII Богд Жавзандамба монголын улс төрийн хошуучлагч болох нь Хураангуй: VIII Богд Жавзандамба хутагт бол Монгол Улсаа эрх чөлөөтэй, тусгаар улс болгоход чухал үүрэг гүйцэтгэсэн төрийн зүтгэлтэн юм. Тэрээр 1900-аад оноос эхлэн үндэсний эрх чөлөө, тусгаар тогтнолоо баталгаажуулах гадаад, дотоод бодлогыг тууштай явуулж, үр дүнд хүрч, амжилт олсон билээ. Жавзандамба хутагт шашны зүтгэлтэн төдийгүй улс төрийн хошуучлагч, нийгмийн оюун санааны удирдагч байв. Бид энэхүү өгүүлэлдээ түүнийг “улс төрийн хошуучлагч” талаас нь тодотгон гаргахыг зорьсон болно. XX зууны эхэн гэхэд Ар Монгол төдийгүй монгол туургатанд хүлээн зөвшөөрөгдсөн нэр хүнд, нөлөө бүхий шашин, улс төр, нийгмийн зүтгэлтэн бол Жавзандамба хутагт байв. Түүнд нийгмийн оюун санааг удирдан чиглүүлэх хүч нөөцөөс гадна захирах хамжлага, шавь нар, дэмжигч сүсэгтэн, ард иргэдийн тойрон хүрээлэл байжээ. Мөн Манж Чин гүрний төрд зүтгэж байсан хэдий боловч тусгаар тогтнолоо сэргээн мандуулах зорилго бүхий монгол ноёд, төр, цэрэг, шашны зүтгэлтнүүдийн дэмжлэг юм. Тэдний үзэл бодол, зорилгыг нэгэн зүгт хандуулж, нэгтгэн зангидаж чадсанд 1911 оны үндэсний эрх чөлөөний хувьсгалын ололт, амжилт, үнэ цэн оршиж байгаа ажээ. Жавзандамба хутагтын улс төрийн бодлого нь Чин ван Ханддорж, Да лам Цэрэнчимэд, Сайн ноён хан Намнансүрэн, Түшээ гүн Чагдаржав, Хайсан гүн зэрэг хамтран зүтгэгч сайд нарын гадаад, дотоодод явуулсан улс төр, эдийн засаг, цэрэг дайны үйл ажиллагаагаар тодрон илэрч байна. Түүхэн үйл явдлуудаас үзэхэд зөвхөн Ар Монголоор хязгаарлаад зогсохгүй, Өвөр Монгол, Буриад, Тагна урианхайг нэгтгэсэн “Монгол туургатан”-ны улс байгуулахыг зорьж байжээ. Энэхүү зорилго нь бүрэн дүүрэн